LoRa Based Soil Quality Monitoring for Purple Eggplant Cultivation: Pemantauan Kualitas Tanah Berbasis LoRa untuk Budidaya Terong Ungu - Himawan Nugroho; Shazana Dhiya Ayuni (Indonesian Journal of Innovation Studies, 2025)
General Background: Soil quality is a critical factor in agricultural production because soil moisture, pH, and environmental conditions influence plant growth and crop management. Specific Background: Recent technological developments have enabled the application of Internet of Things (IoT) systems and Long Range (LoRa) communication for remote agricultural monitoring. Knowledge Gap: Many purple eggplant farmers still lack practical guidance and real-time tools to assess soil conditions accurately, creating challenges in maintaining suitable growing environments. Aims: This study aims to develop a LoRa-based soil quality monitoring system for purple eggplant cultivation using soil moisture, soil pH, and DHT22 sensors integrated with ESP32 and Telegram-based monitoring. Results: The developed system successfully collected and transmitted soil and environmental data through LoRa communication to a receiver and Telegram platform. Sensor readings indicated stable soil pH values of 7.79 and soil moisture levels of 88.8, while environmental parameters were monitored in real time. Novelty: The study integrates multiple soil and environmental sensors with LoRa wireless communication and Telegram-based monitoring into a single system designed for purple eggplant cultivation. Implications: The system provides continuous information on soil and environmental conditions, supporting farmers in monitoring cultivation areas and reducing risks associated with unsuitable soil conditions while facilitating more informed agricultural management decisions.Highlights: Real-time transmission of field measurements was achieved through long-range wireless communication. Integrated sensing captured acidity, moisture status, temperature, and humidity conditions simultaneously. Telegram-based access enabled remote observation of cultivation area parameters using smartphones. Keywords: LoRa; Soil Quality Monitoring; Internet of Things; Purple Eggplant; Wireless Sensor Network